2020
DOI: 10.3390/ijms21186505
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Gossypium barbadense Mutant Library Provides Genetic Resources for Cotton Germplasm Improvement

Abstract: Allotetraploid cotton (Gossypium hirsutum and Gossypium barbadense) are cultivated worldwide for its white fiber. For centuries, conventional breeding approaches increase cotton yield at the cost of extensive erosion of natural genetic variability. Sea Island cotton (G. barbadense) is known for its superior fiber quality, but show poor adaptability as compared to Upland cotton. Here, in this study, we use ethylmethanesulfonate (EMS) as a mutagenic agent to induce genome-wide point mutations to improve the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Two color mutants were selected for re-sequencing at the genome-wide level and the results showed that the SNP identified were distributed evenly on the three chromosomes. However, the mutation densities in the two color-mutants were 3SNV/Mb and 7SNV/Mb, which were lower than those of higher plants, such as 1/11.8 kb in soybean (Li et al, 2017), 181.7 SNP/Mb in cotton (Abid et al, 2020), 1/213 kb in foxtail (Sun et al, 2019), 1/309.5 kb in rice (Guo et al, 2021), 1/89 kb in Arabidopsis thaliana [4]. Generally, the mutation frequency could be increased due to genetic…”
Section: Discussionmentioning
confidence: 80%
“…Two color mutants were selected for re-sequencing at the genome-wide level and the results showed that the SNP identified were distributed evenly on the three chromosomes. However, the mutation densities in the two color-mutants were 3SNV/Mb and 7SNV/Mb, which were lower than those of higher plants, such as 1/11.8 kb in soybean (Li et al, 2017), 181.7 SNP/Mb in cotton (Abid et al, 2020), 1/213 kb in foxtail (Sun et al, 2019), 1/309.5 kb in rice (Guo et al, 2021), 1/89 kb in Arabidopsis thaliana [4]. Generally, the mutation frequency could be increased due to genetic…”
Section: Discussionmentioning
confidence: 80%
“…In the realm of cotton research, notable advancements have been achieved in the development of EMS-induced mutant libraries within diverse cotton species, such as G. arboreum ( Kong et al., 2017 ), G. barbadense ( Abid et al., 2020 ), G. hirsutum ( Lian et al., 2020 ; Wei et al., 2022 ), and G. herbaceum ( Kumar et al., 2022 ). It is noteworthy that the primary focus of these events centered on conventional cultivated G. hirsutum varieties.…”
Section: Ems-induced Mutant Libraries In Cottonmentioning
confidence: 99%
“…The subsequent crucial step involves conducting preliminary experiments to ascertain the optimal concentration of EMS and the necessary treatment duration. It’s crucial to note that due to the distinctive chemical properties of EMS, utilizing a concentration that is too low may result in an insufficient mutation rate, whereas excessively high concentrations can induce plant mortality and impede seed germination ( Abid et al., 2020 ).…”
Section: Ems-induced Mutant Libraries In Cottonmentioning
confidence: 99%
See 1 more Smart Citation
“…Сорт хлопчатника «Lumian 1» с высокой и стабильной урожайностью был успешно создан путем рентгеновского мутагенеза гибридного потомства линий «Zhongmian 2» и «1195» [13]. В последние годы путем космического мутагенеза также был получен ряд мутантов [15]. Например, Song и др.…”
unclassified